PENGARUH KEBIJAKAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PROYEK KONSTRUKSI PADA PT. MULTI JAYA CONCEPTS DI SAMARINDA - HS, Syamsurahman (EKONOMIA, 2014)
Safety and health maintenance programs, including one in the company,  The implementation of occupational safety and health program for employees is essential as it aims to create a system of safety and occupational health management, involving elements, labor, conditions, communication and integrated working environment in order to reduce accidents.            This study aims to analyze the influence of occupational health and safety policies on employee performance in the construction of PT. Multi Jaya Concepts disamarinda, formulation of the problem in this research is "whether the factor of safety and occupational health composed of top management commitment, regulations and procedures K3, communication, competence of workers, work environment, and worker involvement affect the performance of employees, and to analyze whether the most dominant factor affecting the performance of construction project employees "            The data obtained in this study by the results of questionnaires, observations, interviews and direct observations. by testing the validity, reliability testing as well as the classic assumption test, by means of multiple linear regregsi analysis, F test, a test of determination R2, r correlation test and t-test.            F-test results suggested a positive and significant effect of the independent variables consisting of the Top management commitment, regulations and procedures K3, communication, competence of workers, work environment, and worker involvement on the dependent variable (employee performance kontsruksi).            T-test result declared no significant effect partially dependent variable consisting of top management commitment, regulations and procedures K3, communication, competence of workers, work environment, and worker involvement on employee performance construction project.And most dominant variable effect on employee performance construction project is the involvement of workers.